Parental perceptions and the counselor role in kindergarten transition practices - Lane, Jessica J. (Kansas State University, 2012)
Successful transition practices are essential in moving students forward into new facets of learning and life. Noteworthy is the transition into kindergarten, as students experience a new environment, with new academic, social, and behavioral expectations. Research has reviewed teacher and student perceptions on this topic, but has traditionally overlooked the parent stakeholder. Specifically assessing kindergarten transition from parents’ vantage point provides a varied and necessary perspective that is often underutilized in effective school transitioning programs. Therefore, this study surveyed parents of children transitioning into kindergarten to identify their experiences and involvement in transition programming. Specifically to: (a) assess the concerns of parent stakeholders upon transitioning their children into formal schools (b) assess the perceptions of parent stakeholders in regards to their children’s transition into kindergarten, (c) assess the areas in which parent participants would like more information about the transition process, and (d) explore environmental variables and demographics that may impact student transitional success. The study utilized a retrospective pretest survey design to examine the experiences and perceptions of parents whose children were enrolled in full-day kindergarten in two school districts of comparable size in Northeast Kansas. A sample size of 91 participants was generated, as a parent or guardian of every student enrolled in kindergarten for the 2010-2011 school year in the surveyed schools was selected and solicited as participants for this retrospective pretest study. The final study population included 68 participants (n = 68) amongst the two respective schools, for an overall response rate of 74.7%. Survey mean results indicated that no particular item in academic, behavioral, or social domains were considered a great concern for parents transitioning their child into kindergarten. However, items that received the highest rating for concern prior to kindergarten were in the areas of academic success in comparison to peers, and adjusting to new routines and surroundings. Parents also rated adjusting to new routines and surroundings as the area with the least amount of transitional success. Seventy-three percent of participants agreed or strongly agreed to feeling engaged in the transitional process. Also, a significant difference in parents’ perceived need for both social and behavioral support emerged between first and second born children as they transition into formal schooling indicating parents of firstborn would like more information and support. Finally, results also showed that significance emerged between parents’ desire for counselor services and their concern as to the child’s level of behavioral success upon entering kindergarten.
Keywords: Kindergarten transition; Elementary school counseling; Education; Parent concerns; Transition; Early childhood education; Early Childhood Education (0518)